PENGARUH LEVERAGE, UKURAN PERUSAHAAN, CAPITAL INTENSITY, PROFITABILITAS DAN BIAYA OPERASIOANL TERHADAP PAJAK PENGHASILAN BADAN - Tasrullah, Tatang; Zulaecha, Hesty Ervianni; Hidayat, Imam; Kimsen, Kimsen (Jurnal Ilmiah Ilmu Manajemen, 2022)
The purpose of this study is to examine the effect of Leverage, Company Size, Capital Intensity, Profitability and operating costs on Corporate Income Tax. The population in this study consisted of coal mining sub-sector companies listed on the Indonesia Stock Exchange in 2015-2019. A sample of 8 companies used in this study was determined by the purposive sampling method. The data used are secondary data. Data analysis was performed with descriptive statistics using panel data regression analysis techniques. The empirical results of this study indicate that Leverage has a significant positive effect, and Firm Size has a significant negative effect. Meanwhile, Capital Intensity, Profitability and operating costs have no effect on Corporate Income Tax.